The drivers of change: The role of peasants in the creation of an agro-ecological agriculture - Douwe van der Ploeg, Jan (Agroecología, 2011)
This article discusses the interrelations between peasantry, agro-ecology and the current process of re-peasantization that emerges as the highly differentiated set of responses peasants use to face, and to respond to, the current agrarian crisis. A key argument is that agro-ecology needs the peasantries of both the North and the South as decisive social carriers.